ANALYSIS OF THE IMPACT OF THE COVID-19 PANDEMIC ON UMKM AND ADAPTATION STRATEGIES: A LITERATURE REVIEW - Gunawan Widjaja (CV. Adiba Aisha Amira, 2024)
The COVID-19 pandemic has changed the global economic landscape, having a significant impact on various sectors, including Micro, Small and Medium Enterprises (MSMEs). This study aims to systematically analyse and review the impact of the COVID- 19 pandemic on MSMEs and identify adaptation strategies implemented by MSMEs in the face of this crisis. The results showed that the COVID-19 pandemic brought severe economic challenges to MSMEs, including decreased turnover, disruptions in the supply chain, and difficulties in accessing finance. However, the study also found that MSMEs that were able to adapt quickly, such as through business digitalisation, product diversification, and the use of e-commerce platforms, were able to minimise the negative impacts and even find new opportunities in the crisis. Based on this analysis, it is concluded that government support and access to resources are key in increasing MSMEs' resilience to the impact of the pandemic. This research provides insights for policymakers, practitioners, and academics in developing effective strategies and interventions to support MSMEs in the pandemic era and beyond.